Characterization and elemental quantification of natural hydroxyapatite produced from cow bone - Akindoyo, John Olabode; Suriati, Ghazali; Beg, M. D. H.; Jeyaratnam, N. (2018)
Demand for hydroxyapatite (HA) is increasing annually, due to the growing number of orthopedic patients. Therefore, there is a challenge of meeting this growing demand without interfering with the integrity of the environment. The aim of this study is to produce HA from natural sources. In this study, natural HA was extracted from cow bone through ultrasound treatment of the raw bone followed by calcination at different temperatures from 650-950 oC [1, 2]. Ultrasound treatment in ordinary water medium is found to be suitable for cleaning the bone and the HA produced after calcination at 950 oC was found to possess the desirable properties needed for pure HA.